Employability of Senior High School Technical-Vocational and Livelihood Graduates: Basis for Human Resource Management Enhancement Program) - Raymund A. Dela Cruz (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study examined the employability of Senior High School graduates in the Technical-Vocational and Livelihood Track at Malandag National High School and Alabel National High School from batches 2018, 2019, and 2020. The participants were chosen using the purposive sampling technique within the descriptive survey design; a total of two hundred ninety-three (293) graduates responded by filling out the adapted Graduate Tracer Study survey questionnaire. They responded to an online survey questionnaire, and the collected data was analyzed descriptively using frequency and percentages, means and weighted means, t-test, and analysis of variance as statistical treatments. The majority of graduates are employed, with 202 (68.9%) in service and sales industries, while 91 (31.1%) were unemployed despite having attended college, lacked experience, and had family concerns. Work-related issues were the most common challenge faced by graduates. The study found no significant differences in employability across sex, location, strand, or field of specialization.